The role of the muscular system in the pathogenesis of thrombotic complications of the lower extremities in cancer patients - Petro Bodnar (The Journal of V.N. Karazin Kharkiv National University. Series "Medicine" (Online), 2021)
Introduction. Thrombosis occurs in 15 % of cancer patients, most of these thrombosis is localized in the venous system of the lower extremities. In addition to biological and chemical factors that increase thrombosis, changes in the muscles of the lower extremities play an important role. Disorders of hemodynamic and metabolic processes in the muscles of the lower extremities lead to morphological changes and increase the risk of thrombosis in cancer patients. The aim of the study. Investigate morphological changes in the muscles of the lower extremities and evaluate their role in the formation of thrombosis in cancer patients. Materials and methods. Histological examination of 90 patients, which were divided into four groups depending on the location of the cancer process and the cause of death. The first group A – 34 patients with colon cancer, the second group B – 20 patients with pancreatic cancer, patients from these groups died as a result of thromboembolism. Group B – 19 patients, and group G – 17 patients - people whose cause of death was not thromboembolism. The analysis of biomaterial by means of histological and polarization methods of research is carried out. Additionally, electron microscopy of the obtained biopsy materials was performed. The number of citrate blood endothelial cells was determined in all subjects according to the method of J. Hladovez. Research results and their discussion. The study revealed a large number of morphological changes in blood vessels and muscle fibers. The data obtained indicate that patients with cancer of the pancreas and colon have significant changes in the endothelial lining of the venules and areterioles. All cells have signs of interstitial edema, changes in organelles and signs of hemodynamic disturbances. In some areas, there were complete atrophy of some muscle fibers and compensatory hypertrophy of others. Studies have shown areas of sarcoplasmic homogenization and myocytolysis. Conclusions. In the case of cancer of the pancreas or/and colon, there is significant damage to the endothelium of the vessels of the lower extremities, there are dystrophic-atrophic changes in the muscles with impaired function. Cells suffer from interstitial and perivascular edema, there are contractures of change, myocytolysis. Morphological changes lead to disruption of their function of damage, myocytolysis and remodeling of muscle fibers. The result is an increased risk of thrombosis with subsequent thrombus consideration and a possible risk of pulmonary embolism.